PENYULUHAN PENANGANAN PASCA PANEN DAN PENGOLAHAN UBI JALAR UNGU BAGI SISWA SMK NEGERI 1 BAWEN KABUPATEN SEMARANG - Putri, Aldila Sagitaning; Larasati, Dewi; Sani, Elly Yuniarti (STIE Pelita Nusantara, 2023)
SMK Negeri 1 Bawen is located in the Bawen District area which is located in Semarang Regency and has six Expertise Programs, namely the Agricultural Product Agribusiness Expertise Program, Plant Production Agribusiness, Livestock Production Agribusiness, Agricultural Mechanization, Culinary Planning and Tourism. graduates of SMK Negeri 1 Bawen are scattered throughout the archipelago and work in various sectors of the Business and Industry World. This community service activity aims to provide information to students at SMK Negeri 1 Bawen Semarang Regency about the importance of post-harvest handling of purple sweet potatoes and how to process them and provide skills on how to process purple sweet potatoes into purple rice and purple sweet potato ice cream. The partner's problem is that so far purple sweet potato has not been diversified, so this extension activity will increase knowledge about purple sweet potato processing. The activities carried out in the community service program entitled